Konsep Iqra’ dalam Q.S Al-Alaq dan Relevansinya Terhadap Minat Baca Mahasiswa Universitas Islam Negeri Sumatera Utara di Era Digital - Dewi, Fira Afrina; Muftiah, Napizah; Suci, Vhinka Frithzy; Tarigan, Mhd Rafi’i Ma’arif (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The background of this research is based on the declining interest and enthusiasm for reading among university students, which is further exacerbated by the rise of digital distractions and the increasing dependence on instant information and artificial intelligence (AI) technology. This study aims to examine the concept of Iqra’ in Q.S. Al-‘Alaq and its relevance as a foundation for spiritual and intellectual motivation in enhancing the reading interest of undergraduate students in Qur’anic Studies (Ilmu Al-Qur’an dan Tafsir) at the State Islamic University of North Sumatra in the digital era. This research employs a mixed-methods approach, combining quantitative and qualitative methods. The quantitative approach is used to measure students’ reading interest through the distribution of Likert-scale questionnaires, while the qualitative approach explores in-depth factors influencing this phenomenon through interviews and observations. The research population consists of Qur’anic Studies students at the State Islamic University of North Sumatra. The sample is selected using purposive sampling, considering students’ involvement and experience in literacy activities and digital media use. The study indicates that the concept of Iqra’ can encourage students’ reading interest; however, institutional support and literacy programs are needed to ensure sustainable impact.